Safety and immunogenicity of the therapeutic vaccine TG1050 in chronic hepatitis B patients: a phase 1b placebo-controlled trial. Issue 2 (1st February 2020) - Zoulim, Fabien; Fournier, Claire; Habersetzer, François; Sprinzl, Martin; Pol, Stanislas; Coffin, Carla S; Leroy, Vincent; Ma, Mang; Wedemeyer, Heiner; Lohse, Ansgar W; Thimme, Robert; Lugardon, Karine; et al.
ABSTRACT: Treatment of chronic hepatitis B (CHB) typically requires life-long administration of drugs. Cohort and pre-clinical studies have established the link between a functional T-cell-mounted immunity and resolution of infection. TG1050 is an adenovirus 5-based vaccine that expresses HBV polymerase and domains of core and surface antigen and has shown immunogenicity and antiviral effects in mice. We performed a phase 1 clinical trial to assess safety and explore immunogenicity and early efficacy of TG1050 in CHB patients. This randomized, double blind, placebo-controlled study included two sequential phases: one single dose cohort (SD, n = 12) and one multiple (3) doses cohort (MD, n = 36). Patients, virally suppressed under nucleoside(d)tide analog NUC therapy, were randomized 1:1:1 across 3 dose levels (DL) and assigned to receive 10 9, 10 10, 10 11 virus particles (vp) of TG1050 and then randomized within each DL to placebo (3:1 and 9:3 vaccines/placebo in each DL, respectively, for the SD and MD cohorts). Cellular (ELISPOT) and antibody responses (anti-Adenovirus), as well as evolution of circulating HBsAg and HBcrAg, were monitored. All doses were well tolerated in both cohorts, without severe adverse event. TG1050 was capable to induce IFN-γ producing T-cells targeting 1 to 3 encoded antigens, in particular at the 10 10 vp dose. Overall, minor decreases of HBsAg were observed while a number of vaccinees reached unquantifiable HBcrAg by end of the study. In CHB patients under NUC, TG1050 exhibited a good safety profile and was capable to induce HBV-specific cellular immune response. These data support further clinical evaluation, especially in combination studies.